Taking a hands-on approach: Current perspectives on the effect of hand position on vision - Philip Tseng (Frontiers Research Topics, 2015)
An exciting new line of research that investigates the impact of one's own hands on visual processing has flourished in the past several years. Specifically, several studies have demonstrated that objects near the hands receive prioritized attention, enhanced perceptual sensitivity, altered figure-ground assignment, prolonged and detail-oriented processing, and improved visual working memory. Taken together, these results demonstrate that the visual system reveals a new pattern of processing when one's hands are in proximity of viewed objects. Therefore, the vast majority of studies on visual processing, in which one's hands are kept away from the stimuli, may constitute but one side of a more complex story of the inner workings of the visual system. With several consistent behavioral demonstrations of hand-altered vision now in the literature, the present challenge facing this growing field, and the aim of this Research Topic, is four-pronged: 1) Isolate and elucidate the underlying cognitive and neural mechanisms of hand-altered vision; 2) Map the parameters and conditions of hand-nearness that permit/prevent the onset or maintenance of hand-altered vision; 3) Determine the consequences of hand-altered vision for higher-level cognition and assess its applied potential (e.g., as a neuropsychological intervention); and, 4) Present a cohesive and predictive theoretical account of hand-altered vision. We welcome submissions that fit into any one (or a combination) of the above domains. For behavioral research, we particularly encourage submissions that are relevant to the advancement of our understanding of the neural mechanisms of hand-altered vision (e.g., demonstrations that might corroborate or disconfirm proposed neural systems).